Prevalence and Antimicrobial-Resistance of Staphylococcus aureus Isolated from Blood Culture in University Hospital, Turkey - Calik Zeki; Karamese Murat; Acar Osman (Global Journal of Infectious Diseases and Clinical Research - Peertechz Publications, 2015)
Introduction: In this study, our aim was to detect the prevalence and antibiotic resistance of Staphylococcus aureus, isolated from blood culture in Kafkas University Hospital, Kars, Turkey retrospectively and to present the first data from this university hospital. Materials and Methods: Total 1456 blood culture bottles were sent to Microbiology Laboratory of between January-2013 and December-2014. All bottles were placed into Automated Blood Culture System. After the positive bottles were detected by machine, the bacteria were identified and antibiotic susceptibility tests were performed by using both Microorganism Identification System and Kirby-Bauer Disk Diffusion method. Results: Total 63 Staphylococcus aureus positive samples were detected. Interestingly, 32 (50.8%) of total Staphylococcus aureus positive samples were Methicillin-Resistant Staphylococcus aureus and 31 (49.2%) of them were Methicillin-Sensitive Staphylococcus aureus. When the antibiotic resistance profiles were checked, it was seen that 29 Staphylococcus aureus strains were only resistant to Erythromycin and 18 strains were only resistant to Clindamycin whereas 10 strains were resistant both to Erythromycin and Clindamycin. Conclusions: The antibiotic resistance is getting increased by uncontrolled antibiotic usage and wrong choices in empiric therapy day by day. Each hospital has to detect its own antibiotic resistance profiles and apply empiric therapy according to these profiles.